Loan-to-value policy and housing finance: Effects on constrained borrowers - de Araujo, Douglas Kiarelly Godoy; Barroso, Joao Barata Ribeiro Blanco; Gonzalez, Rodrigo Barbone (Journal of Financial Intermediation, 2020)
This paper explores the effects of an LTV limit on constrained borrowers using comprehensive loan- and borrower-level data from Brazil. LTV limits entail identification challenges because constrained borrowers are no longer directly observed after the policy is implemented. In this paper, partially observed treatment status is addressed by an adjusted difference-in-difference method, focusing on the average treatment effect on the treated (ATT) borrowers (i.e. those that would violate the LTV limit if unconstrained). In the most affected segment, treated individuals cope with the new LTV limit by making higher down payments and also purchasing more affordable houses. They are also less likely to be in arrears, suggesting that LTV limits are effective macroprudential tools by lowering the risk of some originated housing loans.